2015
DOI: 10.1002/cbdv.201400255
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of the Aerial Parts of Pulicaria sicula (L.) Moris Growing Wild in Sicily: Chemotaxonomic Volatile Markers of the Genus PulicariaGaertn.

Abstract: The chemical composition of the essential oil isolated from the aerial parts of Pulicaria sicula (L.) Moris was characterized by GC-FID and GC/MS analyses. The oil was particularly rich in oxygenated terpenoids. Among the oxygenated monoterpenes (content of 44.5%), the most abundant were borneol (23.7%), bornyl acetate (6.5%), and isothymol isobutyrate (6.2%). Caryophyllene oxide (10.2%), caryophylladienol I (4.3%), and caryophylla-3,8(13)-dien-5β-ol (4.4%) were identified as the main constituents among the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…(wild tea) [29,30], P. jaubertii [16], P. mauritanica (Ifenzi oudaden) [31,32], P. odora (L.) Rchb. (Mediterranean fleabane) [18], P. sicula (L.) Moris (fleabane) [33], P. stephanocarpa Balf.f. (derbeb) [17], P. undulata [34][35][36][37], and P. vulgaris Gaertn.…”
Section: Treatment Of Datamentioning
confidence: 99%
“…(wild tea) [29,30], P. jaubertii [16], P. mauritanica (Ifenzi oudaden) [31,32], P. odora (L.) Rchb. (Mediterranean fleabane) [18], P. sicula (L.) Moris (fleabane) [33], P. stephanocarpa Balf.f. (derbeb) [17], P. undulata [34][35][36][37], and P. vulgaris Gaertn.…”
Section: Treatment Of Datamentioning
confidence: 99%
“…(−)-β-caryophyllene (BCP), a functional non-psychoactive CB2 receptor agonist [12,13,14], is found in, for example, plant-derived oleoresins, essential oils, solutes, distillates, extracts, fermentations, infusions, and leachates, from several plants [15,16,17,18,19,20,21,22,23,24,25]. Furthermore, BCP showed analgesic, anti-inflammatory, neuroprotective, anti-depressive, anxiolytic, and anti-nephrotoxicity effects [12,13,26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…for 21.7%), shows a complete different chemical profile of the two taxa. Although the huge presence of thymol derivatives as in P.v., with the exception of P. arabica collected in Tunisia (Abed et al 2010), is not a common feature in Pulicaria genus (Maggio, Riccobono, et al 2015), the occurrence of carvotanacetone has been reported in several taxa such as P. jaubertii collected in S. Arabia (98.6%) (Fawzy et al 2013 (Algabr et al 2012) and P. arabica collected in Tunisia (3.5%) (Abed et al 2010), whereas b-caryophyllene, the second most abundant compound of P.v.g., is present in good quantity in P. dysenterica collected in Greece (Basta et al 2007) and P. stephanocarpa collected in Soqotra (Ali, Crouch, et al 2012). Finally, geranyl propionate (8.2% in P.v.g.…”
mentioning
confidence: 94%
“…graeca with those reported for the essential oil of P. vulgaris Gaertner (P.v.) (Sharifi-Rad et al 2014) and of all the other taxa of Pulicaria studied so far, recently reviewed (Maggio, Riccobono, et al 2015), shows some interesting points.…”
mentioning
confidence: 94%